Pengaruh Quick Ratio, Return On Assets, Net Profit Margin, Dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Sektor Industri - Baining, Mellya Embun; Laily Ifazah; Trianawati, Trianawati (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of Quick ratio, Return on assets, Net profit margin, and Earning per share on stock prices in the Industrial Sector listed on the Indonesian Sharia Stock Index (ISSI) in 2020-2024 simultaneously and partially. The approach used is quantitative. The data for this study are secondary data obtained from the official website of the Indonesia Stock Exchange. Sampling was carried out by purposive sampling and obtained 15 Industries listed on the ISSI for the period 2020 - 2024. Data analysis used Panel Data Regression Analysis using the Eviews Application. The results of the study show: 1) Quick Ratio has no effect on stock prices; 2) Return On Assets has a significant positive effect on stock prices; 3) Net Profit Margin has no effect on stock prices; 4) Earning Per Share has a significant positive effect on stock prices; and 5) Quick Ratio, Return On Assets, Net Profit Margin and Earning Per Share simultaneously have a significant effect on stock prices in Industrial Sector Companies with a determination coefficient value of 71.7078%.